2010
DOI: 10.2319/021210-90.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of soft tissue change gradients after mandibular setback surgery in skeletal Class III malocclusion

Abstract: Objective: To evaluate whether mandibular setback surgery (MSS) for Class III patients would produce gradients of three-dimensional (3D) soft tissue changes in the vertical and transverse aspects. Materials and Methods: The samples consisted of 26 Class III patients treated with MSS using bilateral sagittal split ramus osteotomy. Lateral cephalograms and 3D facial scan images were taken before and 6 months after MSS, and changes in landmarks and variables were measured using a Rapidform 2006. Paired and indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 21 publications
5
50
0
4
Order By: Relevance
“…Lim et al 7 found that 3D soft tissue changes in Class III patients after mandibular setback surgery exhibited increased gradients from the upper lip and lower lip to the chin as well as from the stomodium to the mouth corner. Kim et al 8 suggested that there were significant increases in the upper lip length and decreases in the lower lip length in the large setback, hypodivergent, and genioplasty groups in Class III cases with mandibular setback surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al 7 found that 3D soft tissue changes in Class III patients after mandibular setback surgery exhibited increased gradients from the upper lip and lower lip to the chin as well as from the stomodium to the mouth corner. Kim et al 8 suggested that there were significant increases in the upper lip length and decreases in the lower lip length in the large setback, hypodivergent, and genioplasty groups in Class III cases with mandibular setback surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 3D facial scanning can be regarded as a useful and accurate method with which to measure soft tissue change. Lim et al 7 and Kim et al 8 evaluated soft tissue change in 3D facial scanning images according to the skeletal movement of lateral cephalograms after one-jaw orthognathic surgery (mandibular setback only) in cases involving skeletal Class III malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Both one-and two-jaw orthognathic surgeries for Class III correction result in forward and upward movement of the nasal tip (Jung et al, 2009;Lim et al, 2010;Park et al, 2012a) that results from remodeling of the perioral musculature (Jung et al, 2009). The other primary change in nasal esthetics after two-jaw surgery results from malpositioning that 3D imaging now is able to detect more precisely.…”
Section: Middle Third Of the Facementioning
confidence: 98%
“…Even with isolated mandibular setback, the upper lip moves backward (Hershey & Smith, 1974;Suckiel & Kohn, 1978;Sung et al, 2000;Lim et al, 2010;Kim et al, 2012) because both the upper and lower lips are influenced by the protruded mandibular incisors. With the posterior positioning of the mandible, the maxillary incisors rather than the mandibular incisors begin to provide the main support for the upper lip, resulting in an overall reduction in the sagittal projection of the upper lip (Lim et al, 2010). In contrast, due to the LeFort I advancement in two-jaw surgery, the upper lip moves forward (Jensen et al, 1992;Kim et al, 2012).…”
Section: Middle Third Of the Facementioning
confidence: 99%
See 1 more Smart Citation